Carbon-assisted growth of equiangular 2D hexagons of AlN - Nersisyan, Hayk; Thanh, Nam Huynh; Lee, Jong Hyeon; Suh, Hoyoung; Hong, Soon Jik (Elsevier BV, 2022)
This paper describes a promising approach to synthesize equiangular 2D hexagons of AlN by carbon-assisted combustion of Al-0.1AlF3 mixture in a nitrogen atmosphere. Two-dimensional hexagons with thicknesses ranging from 0.05 to 5 mu m and lateral sizes ranging from 0.5 to 150 mu m are successfully produced at the 1800-1950 degrees C temperature range. It was shown that the formation of 2D hexagons occurs through carbonaceous phases of aluminum involving aluminum carbide (Al4C3) and carbonitrides (AlCxN1-x).